2023
DOI: 10.3390/antiox12111953
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of GSH in Keeping the Redox Balance in Mammalian Cells: Mechanisms and Significance of GSH in Detoxification via Formation of Conjugates

Sofia K. Georgiou-Siafis,
Asterios S. Tsiftsoglou

Abstract: Glutathione (GSH) is a ubiquitous tripeptide that is biosynthesized in situ at high concentrations (1–5 mM) and involved in the regulation of cellular homeostasis via multiple mechanisms. The main known action of GSH is its antioxidant capacity, which aids in maintaining the redox cycle of cells. To this end, GSH peroxidases contribute to the scavenging of various forms of ROS and RNS. A generally underestimated mechanism of action of GSH is its direct nucleophilic interaction with electrophilic compounds yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 250 publications
(284 reference statements)
0
3
0
Order By: Relevance
“…It protected cells from damage by free oxides, such as ROS. 29 GSH, a product of cystine/glutamate reverse transporter, also acted as a substrate for GPX4. 30 GPX4 was believed to be a key regulator of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It protected cells from damage by free oxides, such as ROS. 29 GSH, a product of cystine/glutamate reverse transporter, also acted as a substrate for GPX4. 30 GPX4 was believed to be a key regulator of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione was a peptide containing cysteine, which was considered to be the main REDOX substance in cells. It protected cells from damage by free oxides, such as ROS . GSH, a product of cystine/glutamate reverse transporter, also acted as a substrate for GPX4 .…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with previous research demonstrating STAT3 as a key regulator of astrocyte ROS detoxification and gene expression of antioxidant defenses [ 6 ]. Inhibition of STAT3 significantly reduced basal antioxidant capacity in our study, potentially due to its role in regulating GSH levels, a major contributor to cellular antioxidant capacity [ 67 ]. Supporting this notion, a previous study showed that conditional knockout of STAT3 or pharmacological inhibition of Jak2, which prevents STAT3 activation, results in a significant reduction of GSH levels in astrocytes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSH, a major constituent of the non-enzymatic antioxidant system, plays a crucial role in cellular redox balance by scavenging various forms of ROS and reactive nitrogen species (RNS) (Bansal & Simon, 2018;Georgiou-Siafis & Tsiftsoglou, 2023;Kennedy et al, 2020). NRF2 is a major antioxidant transcription factor that plays a key role in regulating redox signalling to maintain redox homeostasis and is involved in a variety of cellular processes (Han et al, 2023;Park et al, 2023;Yang & Smith, 2023).…”
Section: Discussionmentioning
confidence: 99%